Widespread and Accelerated Decrease of Observed Mean and Extreme Snow Depth Over Europe. Issue 22 (20th November 2018) - Fontrodona Bach, A.; van der Schrier, G.; Melsen, L. A.; Klein Tank, A. M. G.; Teuling, A. J.
Abstract: Accumulated snow amounts are a key climate change indicator. It combines the competing effects of climate change‐driven changes in precipitation and stronger snowmelt related to increasing temperatures. Here we provide observational evidence from a pan‐European in situ data set that mean snow depth generally decreases stronger than extreme snow depth. Widespread decreases in maximum and mean snow depth were found over Europe, except in the coldest climates, with an average decrease of −12.2%/decade for mean snow depth and −11.4%/decade for maximum snow depth since 1951. These trends accelerated after the 1980s. This has strong implications for the availability of freshwater in spring, while extremes in snow depth, usually very disruptive to society, are decreasing at a slower pace. Plain Language Summary: Changes in snow accumulation are a climate change indicator. Global warming brings more extreme precipitation, and higher temperatures lead to less snow accumulation. Studies of the future climate indicate that under strong warming of the planet, extremes of snowfall will decrease less than the average snowfall. In this study, we show that snow accumulation is already dramatically decreasing over Europe, which has strong implications for the availability of freshwater during the melt period in spring. However, extreme snow accumulation, which is usually very disruptive to society, is decreasing at a slower pace. Key Points: A widespread decrease of mean and extreme snow depth is observed over Europe Extreme snow depth is decreasing less fast than mean snow depth There is an acceleration of the decrease after the 1980s